2018
DOI: 10.1101/449785
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Elevated expression of LGR5 and WNT signalling factors in neuroblastoma cells with acquired drug resistance

Abstract: word count 207 Word count 3,917 Figures 6 2 Abstract Neuroblastoma (NB) is the most common paediatric solid cancer with high fatality, relapses and acquired resistance to drug therapy. The clinical challenge NB poses requires new therapeutic approaches to improve survival rates.The WNT signalling pathway is crucial in embryonic development but has also been reported to be dysregulated in glioblastoma, ovarian, breast and colorectal cancer.LGR5 is a receptor which potentiates the WNT/β-catenin signalling pathwa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 46 publications
0
1
0
Order By: Relevance
“…Similar increased sensitivity and decreased β‐catenin expression were observed in human SH‐SY5Y and IMR32 cells towards DOX after XAV939 treatment (Suebsoonthron et al, 2017). Another study reported that overexpression of LGR5 and Wnt signaling imparted resistance in SH‐SY5Y, IMR‐32 and IMR‐5 cell lines against vincristine (VCR) or DOX (Myssina et al, 2018). The expressions of FZD6, a Wnt receptor, is inversely proportional to the overall survival of NB patients, which developed tumorospheres and aggressive tumors more readily (Aravindan et al, 2019).…”
Section: Wnt Signaling Mediated Chemoresistance In Nbmentioning
confidence: 99%
“…Similar increased sensitivity and decreased β‐catenin expression were observed in human SH‐SY5Y and IMR32 cells towards DOX after XAV939 treatment (Suebsoonthron et al, 2017). Another study reported that overexpression of LGR5 and Wnt signaling imparted resistance in SH‐SY5Y, IMR‐32 and IMR‐5 cell lines against vincristine (VCR) or DOX (Myssina et al, 2018). The expressions of FZD6, a Wnt receptor, is inversely proportional to the overall survival of NB patients, which developed tumorospheres and aggressive tumors more readily (Aravindan et al, 2019).…”
Section: Wnt Signaling Mediated Chemoresistance In Nbmentioning
confidence: 99%